2016
DOI: 10.4995/wrs.2016.4170
|View full text |Cite
|
Sign up to set email alerts
|

Technical note: concentration and composition of airborne aerobic bacteria inside an enclosed rabbit shed

Abstract: Numerous studies have been conducted to analyse bacterial aerosols in animal houses, which is beneficial for the control of animal diseases. However, little information on aerosols in enclosed rabbit sheds was available. An FA-1 sampler was employed to collect air samples in an enclosed rabbit house in the Qingdao region of China. Concentration, composition, and aerodynamics of bacterial aerosols inside the enclosed rabbit shed were systematically analysed. The concentration of airborne bacteria inside the rab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…The higher microbial count in Area 3 may be due to the accumulation of faecal matter and the presence of moisture which favours the multiplication of bacteria at a faster growth. This is in agreement with Li et al, (2016) who showed that a large number of airborne aerobic bacteria were present inside the enclosed rabbit shed and the type of environment may pose a serious threat to the health of exposed animals and individuals. This is in agreement with the findings of Gautam et al, (2011) who mentioned that the slower water replacement and available standing water leads to a greater pathogen load.…”
Section: Fig 2 Bacterial Isolation Kit Used For Identification Of Bsupporting
confidence: 92%
“…The higher microbial count in Area 3 may be due to the accumulation of faecal matter and the presence of moisture which favours the multiplication of bacteria at a faster growth. This is in agreement with Li et al, (2016) who showed that a large number of airborne aerobic bacteria were present inside the enclosed rabbit shed and the type of environment may pose a serious threat to the health of exposed animals and individuals. This is in agreement with the findings of Gautam et al, (2011) who mentioned that the slower water replacement and available standing water leads to a greater pathogen load.…”
Section: Fig 2 Bacterial Isolation Kit Used For Identification Of Bsupporting
confidence: 92%